Thermal kinetics of montmorillonite nanoclay/maleic anhydride-modified polypropylene nanocomposites - Cheng, Henry Kuo Feng (2013)
Thermal kinetics of montmorillonite nanoclay (MMT)/maleic anhydride-modified polypropylene (MAH-PP) composites (PPCNs) is reported here in terms of thermal stability, decomposition, and crystallization kinetics. The effects of MMT nanoclay on the thermal stability of PP in MMT/MAH-PP composites have been examined at different heating rates by means of thermogravimetric (TG) analysis. Based on the TG results, the Ozawa method was applied to determine the activation energies of decomposition for MMT/MAH-PP composites and the results were then verified by the Kissinger method. It was found that the thermal stability of PP was significantly improved in the presence of MMT nanoclay. Differential scanning calorimetry (DSC) was used to study the melting and crystallization behaviors of MMT/MAH-PP composites under various thermal conditions. Using the data from DSC, the Kissinger method was applied to estimate the activation energies of PPCNs which were required during their non-isothermal crystallization. The activation energies of crystallization showed that MMT nanoclay served as a nucleating agent in the non-isothermal crystallization of PP in the PPCNs and as a result, the crystallinity of PP was greatly enhanced. Therefore, the presence of MMT nanoclay in MMT/MAH-PP composites effectively modified the thermal kinetics of PP.